Powering LED from Wi-Fi: A qualitative assessment for rectenna design - Ibrahim, R.B. (Institute of Electrical and Electronics Engineers Inc., 2014)
With vast benefits across various market segments, active RFID tags have shown great potential in the healthcare sector. Battery replacement remains a deterrent towards mass implementation of active RFID tag technology. Within this context, rectenna architecture has been investigated as the RF power transfer mechanism for ultra low power on-body communication. A working prototype consisting of 7-stage Cockroft-Walton voltage multiplier integrated with band pass filter and lowpass filter has successfully been developed on 1.57 mm RT/Duroid 5880 laminate with the goal of prolonging battery lifespan. A qualitative assessment is proposed as means of evaluating rectenna performance with various antenna designs connected to optimized rectifier. Under non-controlled environment, powering an LED from a Wireless Access Point transmitter source can be used to gauge robustness of rectenna system. Antenna with 5 dBi gain was capable of powering LED at 10 cm distance from RF source. Â© 2014 IEEE.